EDUCATION AND TRAINING TO SUPPORT OF THE DUTIES AND FUNGTION OF GOVERMENT HEAD IN THE SUNGAI APIT SUB-DISTRICT IN SIAK REGENCY - PAISA, DHAYYU PUSPITA AIDIL; ", SUJIANTO (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
The village goverment is an extension of government agencies of the central government has a strategic role in the regulation of rural / urban and national development success. To improve productivity and compliance with the duties and functions of a head of the village it takes education and training. Education and training is needed in order to improve the quality of human resources to complete its obligations under the own duties and fungtion. Through effective education and training expected, labor productivity can optimize the village head .This study aims to analyze the education and training to support the implementation of the village chief duties at the Sungai Apit Sub-District In Siak Regency.Implementation of education and training in the Sungai Apit Sub-District In Siak Regency relatively still lacking. Government programs to improve the quality of village governance by holding education and training. It meant giving the sense, that there are elements of concern for increased career and skills and expertise for the successful performance of the village head. The top of good faith to the head of the village should have more morale of the staff village and other villages, because we hope to be a driving force in modernizing the administration of the village for many years is still underdeveloped and slow - walking impressed if do not want to say go in places. It is planned to overcome these problems, which in turn can improve the service and dedication in carrying out the duties village headFactors affecting education and training in order to carry out duties in the village head Sungai Apit Sub-District In Siak Regency is a component in education and training itself. Education and Training is seen as a system, the quality of education and training and assessment problems seen from the components of the input , process and output of trainingKey Word : education, training, duties and fungtion, goverment head